Effect of different environmental conditions on surface crack growth in aluminum alloys (Fracture and Structural Integrity, 2017)
Fatigue surface crack growth is studied through experiments and computations for aluminum alloys D16T and B95AT (analogue of 2024 and 7075 aluminum). Subjects for studies are cylindrical hollow specimens with external semi-elliptical surface crack. The variation of fatigue crack growth rate and surface crack paths behavior was studied under cyclic loading for different environmental conditions. Uniaxial tension tests were carried out at low (-60°C), room (+23°C) and high (+250°C) temperature. For the same specimen configuration and the different crack front position as a function of cyclic loading and temperatures conditions the distributions of governing parameter of the elastic-plastic stress fields in the form of In-factor along various crack fronts was determined from numerical calculations. This governing parameter was used as the foundation of the elastic-plastic stress intensity factor (SIF). Both elastic and plastic SIF approach was applied to the fatigue crack growth rate interpretation. It is found that there is a steady relationship between the crack growth rate and the plastic SIF in the form of general curve within a relatively narrow scatter band for all tested specimens at different temperatures.
Keywords: Surface crack; Aluminum alloys; Crack growth; Environmental conditions; Fatigue fracture diagram; Plastic SIF